PEMBELAJARAN FATHUL QORIB DALAM MENINGKATKAN NILAI-NILAI MODERASI BERAGAMA DI PONDOK PESANTREN - Muawanah, Risatul; Syaehotin, Sayyidah (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to describe the forms of difference and supporting and inhibiting factors in learning the book of Fiqh, namely the book of fathul qorib at the Miftahul Ulum Plerean Sumberjambe Islamic boarding school. The approach in this research is qualitative research. The results of the research show that the values ​​of moderation, namely tolerance, have been taught through the Fathul Qorib book, where in the Fathul Qorib book there are several chapters related to justice, namely the Kitabul Faroid Walwashoya (inheritance) chapter and the jinayah (punishment) chapter. Moderation is very important to apply in everyday life to uphold unity, benefit, goodness and peace. One effort to establish religious moderation can be applied through education, namely including the values ​​of religious moderation in the study of the book Fathul Qorib. The data collection techniques for this research are interviews, observation and documentation. The results of this research explain that the internalization of religious moderation values ​​can be developed through learning the Book of Fatul Qorib, then it can be applied through religious formation carried out through planning, implementation and evaluation of Fathul Qorib learning so that ultimately an attitude of religious moderation is formed in students.